Analisis Multivariat Ketidakpuasan Dalam Sektor Kesehatan Di Daerah Istimewa Yogykarta - ASEP ROKHYADI (Jurnal Perilaku dan Strategi Bisnis, 2017)
The dissatisfaction of the service is a thing that it is not desired by service users. That service providers always and continue to make improvements in the services provided, it can reduce the user of the dissatisfaction. The dissatisfaction of this service is an influenced location service, service failure, the complaints, and also skills. The agencies who using services in the health sector is all of the Regional Hospital located in Yogyakarta. The purpose of this study is to analyze what the location indicator, service failures, complaints and skills have the influence forward the dissatisfaction in the health sector.In this research abaout the dissatisfaction of the services to the health sector using the sampling method is the proportional random sampling. The population of the research are all of people who have ever felt of the service in the region  hospital in Yogyakarta especially, with a total sample of 100 respondents.The collecting of data’s were to  analyzed using the basic assumption (normality), the classical assumption test (multicollinearity, heteroscedasticity, independence/autocorrelation) and multiple linear regression (F test, t test). Based on the results of data analysis it can be concluded that the partial  (t test), there are 3 indicators (1) locations (0.974) (2) service failure (0.798) (3) skills (0.162) it  indicators that was not have a strong influence to the dissatisfaction. The hypothesis of test partial is independent variable just only significant indicator of the complaints (0,000), because the significance of value less than 0.05. the conclution of this research, indicators of complaints is an indicator of the most dominant among the others. Whereas the simultaneous hypothesis of testing from all of significant indicators, because the significance of value less than 0.05.